V. Nabokov wobec II wojny światowej – twórcza recepcja i moralna ocena / V. Nabokov and the Second World War - creative reception and moral evaluation - Monika Grygiel (Language, Culture, Politics)
Vladimir Nabokov - the Russian and American writer is the author of two novelistic anti-utopias: Invitation to a Beheading and Bend Sinister, in which he expressed his political views, although he usually declared himself as an apolitical writer. In both works the author exposes the mechanisms of communism and German fascism, warns readers against the enslavement of totalitarian ideology, against passivity in the face of violence and manipulation. Nabokov’s categorical political views stem from the fact that he experienced the consequences of the Russian Revolution of 1917 and World War II, as a result of which he had to flee, first from his native Russia and then from war-torn Europe. The novel Bend Sinister allows direct association of the world depicted with the reality of persecution and repression under Hitlerism, with the morally distorted system of the police state. Nabokov opposes evil, condemns it in all its forms, advocates good, which cannot be seen in the political reality presented by the writer, in the novel’s totalitarian world. It is the duty of the writer to criticize and discredit criminal political ideologies, Nabokov thus emphasizes the importance of goodness and morality in human life.